2016
DOI: 10.1007/s40094-016-0212-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging on the properties of TiO2 nanoparticle

Abstract: Effect of aging on the properties of titanium dioxide nanoparticles produced by laser ablation process in water is investigated experimentally. The fundamental wavelength of a Q-switched Nd:YAG laser was employed to irradiate a high-purity Ti plate in distilled water at temperatures of 20, 35, 50 and 65°C. Produced nanoparticles were diagnosed by UV-Vis-NIR spectroscopy, X-ray diffraction method, and dynamic light scattering device immediately after production and 1 week after. Bandgap energy of samples was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The cellular complexity and cell architecture of complex in vivo environments remains challenging to be reproduced in vitro, while the limited timeframe that can be explored using common in vitro models represents another obstacle, and is typically even more limited for advanced in vitro systems, as also the tissue slices used for this study (here cultured for up to 72 h). Furthermore, when testing nanomaterials other important factors need to be considered to extract meaningful information, such as the inclusion of corona and additional effects due to ageing of dispersions in biological conditions (Kuchibhatla et al 2012 ; Lesniak et al 2012 ; Monopoli et al 2012 ; Gubicza et al 2013 ; Jasbi and Dorranian 2016 ; Lu et al 2017 ). These factors, altogether, make studies of chronic nanoparticle impact in advanced models highly challenging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cellular complexity and cell architecture of complex in vivo environments remains challenging to be reproduced in vitro, while the limited timeframe that can be explored using common in vitro models represents another obstacle, and is typically even more limited for advanced in vitro systems, as also the tissue slices used for this study (here cultured for up to 72 h). Furthermore, when testing nanomaterials other important factors need to be considered to extract meaningful information, such as the inclusion of corona and additional effects due to ageing of dispersions in biological conditions (Kuchibhatla et al 2012 ; Lesniak et al 2012 ; Monopoli et al 2012 ; Gubicza et al 2013 ; Jasbi and Dorranian 2016 ; Lu et al 2017 ). These factors, altogether, make studies of chronic nanoparticle impact in advanced models highly challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The results are mean and standard error of the mean of three independent experiments. Kruskal-Wallis statistic followed by Dunnett's multiple comparisons test were performed on ΔCt values conditions (Kuchibhatla et al 2012;Lesniak et al 2012;Monopoli et al 2012;Gubicza et al 2013;Jasbi and Dorranian 2016;Lu et al 2017). These factors, altogether, make studies of chronic nanoparticle impact in advanced models highly challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanostructured materials owing to unique physical and chemical characteristics compared with those of the bulk materials have received considerable attentions in recent years [1][2][3]. On the other hand, transition metal oxides semiconducting materials such as MoO 3 , WO 3 and NiO have great potential application in microelectronics and optoelectronics [4][5][6][7][8][9][10][11][12][13][14][15]. Among them, nickel oxide (NiO) has specific properties and diverse applications.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of Fe also attributes to this phenomenon. Jasbi and Dorranian reported ageing decreased the bandgap energy due to size enlargement and phase transition [10]. In another studies by Teck & Ibrahim and Meng et al, they established that doping TiO2 with Fe element showed better absorption in the range 400 to 600 nm [11,15].…”
Section: = Cosmentioning
confidence: 99%